Ferroptosis: the emerging player in remodeling triple-negative breast cancer - Li, Jie; He, Dejiao; Li, Sicheng; Xiao, Jun; Zhu, Zhanyong (Frontiers in Immunology, 2023)
Triple-negative breast cancer (TNBC) is a highly heterogeneous breast tumor type that is highly malignant, invasive, and highly recurrent. Ferroptosis is a unique mode of programmed cell death (PCD) at the morphological, physiological, and molecular levels, mainly characterized by cell death induced by iron-dependent accumulation of lipid peroxides, which plays a substantial role in a variety of diseases, including tumors and inflammatory diseases. TNBC cells have been reported to display a peculiar equilibrium metabolic profile of iron and glutathione, which may increase the sensitivity of TNBC to ferroptosis. TNBC possesses a higher sensitivity to ferroptosis than other breast cancer types. Ferroptosis also occurred between immune cells and tumor cells, suggesting that regulating ferroptosis may remodel TNBC by modulating the immune response. Many ferroptosis-related genes or molecules have characteristic expression patterns and are expected to be diagnostic targets for TNBC. Besides, therapeutic strategies based on ferroptosis, including the isolation and extraction of natural drugs and the use of ferroptosis inducers, are urgent for TNBC personalized treatment. Thus, this review will explore the contribution of ferroptosis in TNBC progression, diagnosis, and treatment, to provide novel perspectives and therapeutic strategies for TNBC management.